2017
DOI: 10.4103/1793-5482.152110
|View full text |Cite
|
Sign up to set email alerts
|

Spinal injury resulting from car accident: Focus to prevention

Abstract: Aim:To determine and compare the patterns of spinal injury in car occupants.Materials and Methods:Retrospective cross-sectional study enrolling all patients with spinal fracture after car accidents, who were admitted to hospital more than 24 h during 2004–2009.Results:The lumbosacral spine was the most commonly involved region (64.8). Six patients had spinal cord injury (6.6%). The majority of the victims were drivers of the vehicle (86.8%) and remaining were passengers. There was a significant difference in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
5
15
0
Order By: Relevance
“…that showed thoracolumbar spine was common area for fracture. Fakharian et al (9). Similar to result of This study, showed that lumbosacral spine was the most commonly involved region (64.8).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…that showed thoracolumbar spine was common area for fracture. Fakharian et al (9). Similar to result of This study, showed that lumbosacral spine was the most commonly involved region (64.8).…”
Section: Discussionsupporting
confidence: 83%
“…Different lifestyle and different regions within a country play a role in the mechanism of trauma (5). Fakharian et al (9) showed that car accident composed 29.9% of all traumatic spinal injuries. Fracture of lumbar vertebra was the most common cause of traumatic spinal injury (24.41%), but a study showed that TSI most common area was thoracolumbar spine fracture (46.9%) such Yousefzadeh et al (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the SCT, the cervical region has also been described in other studies [7,9,11,43] as the most damaged skeletal level, includingafter motorcycle accidents [44]. Concerning accidents involving automobiles, injury in the lumbar region was predominant [12]. The thoracic region is the most affected when related to road accidents in general [45].…”
Section: Discussionmentioning
confidence: 80%
“…Traffic accidents are a major cause of SCT, which, according to Verma et al [9], are responsible for the occurrence of 66.4% of trauma in general, being the main cause of spinal injury [1,10,11]. These types of accidents increase the severity because they trigger associated trauma, more serious injuries and higher mortality [12], besides causing psychological problems such as Posttraumatic Stress Disorder and depression [13,14]. Thus they are a serious public health problem, being associated with economic consequences, disabilities, significant losses for the victim and all the family, influencing quality of life, and may lead to death [15].…”
Section: Introductionmentioning
confidence: 99%